A comparative study on the mechanical properties, autogenous shrinkage and cracking proneness of alkali-activated concrete and ordinary Portland cement concrete. (19th July 2021) - Li, Zhenming; Delsaute, Brice; Lu, Tianshi; Kostiuchenko, Albina; Staquet, Stéphanie; Ye, Guang
Highlights: Alkali-activated concrete (AC) reacts faster than OPC concrete (OC) in the very early age. In later age, however, OC shows higher degree of reaction. AC has lower tensile strength-to-compressive strength ratios than OC. AC shows higher autogenous shrinkage but later cracking time than OC. Nonetheless, the reaction degrees of the two systems at cracking are quite similar. AC shows much larger creep coefficient than OC. Abstract: This study aims to compare the developments of mechanical properties and autogenous shrinkage related properties of alkali-activated materials-based concrete (AC) and ordinary Portland cement-based concrete (OC) against curing age and degree of reaction. Temperature Stress Testing Machines are utilized to monitor the evolution of the internal tensile stress and the cracking occurrence in the restrained concrete. It is found that AC shows lower tensile strength-to-compressive strength ratios than OC. The mechanical properties of both OC and AC can be modelled by a power law against the degree of reaction. AC shows higher autogenous shrinkage, but later cracking than OC when under restrained condition. However, the degrees of reaction at which AC and OC cracked are very similar. From the autogenous shrinkage, the elastic modulus and the self-induced stress, the elastic and creep deformations of the concrete can be calculated. AC is found to show much higher creep coefficient than OC.